2010
DOI: 10.1016/j.scitotenv.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based environmental perspective of manufactured silver nanoparticle in syntheses and applications: A systematic review and critical appraisal of peer-reviewed scientific papers

Abstract: It is expected that the antibacterial property of bulk silver is carried over and perhaps enhanced, to silver nanoparticles. Therefore, when one examines the environmental issues associated with the manufacture and use of silver nanoparticle-based products, the antibacterial effects should always be taken into account particularly at the different stages of the product lifecycle. Currently, there are two arguments in the scientific literature about the mechanisms of antimicrobial properties of silver nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
439
0
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 731 publications
(456 citation statements)
references
References 63 publications
4
439
0
13
Order By: Relevance
“…Consequently, diverse ranges of stabilizing or capping materials are used during the synthesis of silver nanoparticles for their controlled release (Liu et al 2010). Arrays of physical, chemical and biological methods have been used to synthesize and stabilize silver nanoparticles (Tolaymat et al 2010;Saha et al 2010Saha et al , 2011Roy et al 2015). Out of these methods, biosynthesis and biomimetic synthesis processes are most extensively accepted in recent years (Vijayaraghavan and Nalini 2010;Mohanpuria et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, diverse ranges of stabilizing or capping materials are used during the synthesis of silver nanoparticles for their controlled release (Liu et al 2010). Arrays of physical, chemical and biological methods have been used to synthesize and stabilize silver nanoparticles (Tolaymat et al 2010;Saha et al 2010Saha et al , 2011Roy et al 2015). Out of these methods, biosynthesis and biomimetic synthesis processes are most extensively accepted in recent years (Vijayaraghavan and Nalini 2010;Mohanpuria et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sulphate-groups in residue 221 of yeast PDC, which are located in the vicinity of the active site and are involved in the activation by substrate (BABURINA et al, 1994), could also interact with silver ions. This might contribute to the partial loss of PDC activity (TOLAYMAT et al, 2010). The morphological differences between control (no treatment) and treated (15 μg ml -1 silver nanoparticles for 3 min) C. tropicalis TISTR 5350 cells were observed under LV-SEM (Figs 2-3).…”
Section: Time Dependent Interaction Of Silver Nanoparticlesmentioning
confidence: 98%
“…top-down and bottom-up, both of which use physical, chemical and biological methods to produce the NPs 13 . CFS was converted to nano-sized particles by physical method using spray dryer (Labultima, LU-222 advanced, Labultima, Mumbai; vertical co-current type with an evaporation rate of 1000 ml/h fitted with an ultrasonic nozzle).…”
Section: Photorhabdus Luminescens (Thomas and Poinar) Is An Endosymbimentioning
confidence: 99%
“…There have been reports of adulteration from all parts of India [9][10][11][12][13][14][15] . Recently, a report indicated that 25% of the milk samples tested in Maharashtra (India) did not comply with the…”
mentioning
confidence: 99%